Penyuluhan Pengelolaan Limbah Perkebunan Sawit Warga; Potensi Nilai Ekonomis di Desa Beriang Tinggi, Kabupaten Kaur - Nasriel Ikhsan; Aprilia Angraini; Athaya Haura Annasywa Hatuala; Wiranti Diah Wulandari; Hikmatul Hasana; Lora Hardiwiyana; Aulia Salsabila Putri; Yohanis Yarom Mate; Ahmad Ferdy Saputra; Danang Adi Putra (Jurnal Dremi (Demi Pengabdi Masyarakat), 2026)
Oil palm is the primary plantation commodity and the main source of livelihood for the community of Desa Beriang Tinggi, Kaur Regency. However, its cultivation generates substantial amounts of organic waste, particularly Empty Fruit Bunches (EFB) and pruned oil palm fronds, which remain underutilized. This community service activity aimed to identify the types and potential of oil palm plantation waste and to formulate waste management recommendations that are suitable for local farming conditions. Data were collected through structured interviews and field observations involving three oil palm plantation managers, representing diverse plantation sizes and ownership types, with a combined area of approximately 32.5 hectares. The findings revealed that both EFB and oil palm fronds are currently left in piles to decompose naturally. This practice is not due to a lack of farmers' knowledge, but rather to limited access to processing equipment, operational constraints in plantation management, and the absence of extension services or technical assistance that directly reach farmers. Based on an assessment of the waste potential and field feasibility, three waste management methods are recommended: solid composting of oil palm fronds and the structured application of EFB as mulch as the primary priorities, as these methods require neither additional equipment nor capital investment, while the production of liquid organic fertilizer from oil palm fronds is proposed as a medium-term alternative. The implementation of these methods has the potential to reduce the use of chemical fertilizers by approximately 15–30% per growing season while creating additional income opportunities through the sale of organic compost. This activity is expected to serve as a practical reference for both farmers and village authorities in optimizing the sustainable management of oil palm plantation waste.